2019
DOI: 10.1038/s41598-018-37681-6
|View full text |Cite
|
Sign up to set email alerts
|

Lignocellulose utilization and bacterial communities of millet straw based mushroom (Agaricus bisporus) production

Abstract: Agaricus bisporus is in general cultivated on wheat and rice straw in China. However, millet straw is a potential alternative resource for Agaricus bisporus cultivation, but this has hardly been studied. In the present study, the feasibility of millet straw based mushroom production was analyzed by three successive trials. Mature compost demonstrated high quality with total nitrogen, pH, and C/N ratio of 2.0%, 7.5, and 18:1 respectively, which was suitable for mushroom mycelia growth. During composting, 47–50%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 74 publications
2
18
0
1
Order By: Relevance
“…Our previous study ( Cao et al, 2018 ) showed that Thermobispora , Thermopolyspora , Ruminiclostridium , Thermobacillus, and Bacillus were the predominant genera bacteria in Phase I.T and II in wheat straw consistent with the present study. Studies by both Székely et al (2009) and Zhang et al (2019) supported our data as they found that the genera Thermopolyspora , Pseudoxanthomonas, and Thermobifida were more abundance in mature compost. In addition, it has been reported that the genus Thermopolyspora, comprising a cellulolytic actinomycetes species, is highly enriched in mature mushroom compost based on wheat straw ( Zhang et al, 2014 ).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Our previous study ( Cao et al, 2018 ) showed that Thermobispora , Thermopolyspora , Ruminiclostridium , Thermobacillus, and Bacillus were the predominant genera bacteria in Phase I.T and II in wheat straw consistent with the present study. Studies by both Székely et al (2009) and Zhang et al (2019) supported our data as they found that the genera Thermopolyspora , Pseudoxanthomonas, and Thermobifida were more abundance in mature compost. In addition, it has been reported that the genus Thermopolyspora, comprising a cellulolytic actinomycetes species, is highly enriched in mature mushroom compost based on wheat straw ( Zhang et al, 2014 ).…”
Section: Discussionsupporting
confidence: 84%
“…The production of edible fungi has emerged as a potential biological use of agricultural AS, supported by low energy consumption and environmentally impact. Given the large variety of agricultural waste likely to be generated across China, the focus is mainly on the most prominent residues, such as rice straw, wheat straw, rye straw, and banana plant waste ( Zhang et al, 2019 ). Typically, AS are treated as lignocellulosic agricultural byproducts, which comprise stalks, stems, and cobs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oorschot & de Hoog (synonym Malbranchea sulfurea) and Myriococcum thermophilum (Fergus) Aa, which stimulate the mycelial growth and production of A. bisporus (Straatsma et al, 1991(Straatsma et al, , 1994Sánchez, 2007;Sánchez et al, 2008) by reducing the concentration of ammonium, immobilizing nutrients, and producing metabolites that can inhibit competing organisms. After the thermophilic fungi colonize the substrate at 45-50 °C, the substrate is cooled down (Zhang et al, 2019) and thermophiles diminish in activity or die and leave as residues their cell membranes, which are composed of polysaccharides, fatty acids such as linoleic acid and proteins that constitute a rich reserve for A. bisporus (Fermor and Wood, 1991). Alternative methods for substrate preparation without the generation of odor have been studied as an improvement of the traditional method of cultivation with two phases for the white button mushroom (Till, 1962;Sánchez and Royse, 2001;Bechara et al, 2005).…”
Section: Introductionmentioning
confidence: 99%